The Valkyries' loom : the archaeology of cloth production and female power in the North Atlantic - Hayeur Smith, Michèle (University Press of Florida, 2020)
"Michèle Hayeur Smith uses Viking textiles as evidence for the little-known work of women in the Norse colonies that expanded from Scandinavia across the North Atlantic in the 9th century AD"--